Techno-Economic Feasibility Analysis of Concentrated Solar Thermal Power Plants as Dispatchable Renewable Energy Resource of Pakistan: A case study of Tharparkar - Kush Lohana; Aqeel Raza; Nayyar Hussain Mirjat; Suhail Ahmed Shaikh; Shoaib Ahmed Khatri; Wajahat Shabbir (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2021)
Pakistan is identified to be one of the next-11 the top emerging economies of the world after the BRICS. This emphasizes the establishment of a competitive electricity market that can fulfil the demand of the country considering the environmental concerns. In this scenario reliability of power is something that cannot be compromised. Dispatchable power stations play a major role in balancing supply and demand; this balance is essential for maintaining the power cuts free country. All dispatchable power stations incorporate some form of storage particularly thermal or chemical (i.e. a stored fuel). Earlier dispatchable power was regarded as the generation which can start quickly and meet the peak demand requirements but arrival of renewables in power system has increased worth of its presence since it has just not to supply peak demand but also to meet during the unavailability of other renewable energy sources because of their intermittent behavior meanly at times of dark hours and slow wind speed. This study considers the viability of Concentrated Solar Thermal Power in Pakistan and thoroughly analyses several characteristics i.e., Availability of fuel, water, road and communication network, flexibility and environmental impacts of the technology for the cite of Tharparkar.